Estimated Transfer of Perfluoroalkyl Substances (PFAS) from Maternal Serum to Breast Milk in Women Highly Exposed from Contaminated Drinking Water: A Study in the Ronneby Mother–Child Cohort - Blomberg, Annelise J.; Norén, Erika; Haug, Line S.; Lindh, Christian; Sabaredzovic, Azemira; Pineda, Daniela; Jakobsson, Kristina; Nielsen, Christel (Environmental health perspectives, 2023)
Infancy perfluoroalkyl substances (PFAS) exposure from breastfeeding is partially determined by the transfer efficiencies (TEs) of PFAS from maternal serum into breast milk. However, to our knowledge there are no studies of such TEs in highly exposed populations. We estimated the TEs of PFAS from maternal serum into colostrum and breast milk in a cohort of women with a wide range of PFAS exposures. The Ronneby Mother-Child Cohort was established in 2015 after PFAS contamination was discovered in the public drinking water of Ronneby, Sweden. We measured seven PFAS in matched samples of maternal serum at delivery and colostrum and breast milk. We calculated the TE (in percentage) as the ratio of PFAS in colostrum or breast milk to serum multiplied by 100 and evaluated whether TEs varied by PFAS, lactation stage, or exposure level using a series of linear mixed-effects models with a random intercept for each woman. This study included 126 mothers. PFAS associated with firefighting foams [i.e., perfluorohexane sulfonic acid (PFHxS) and perfluorooctane sulfonic acid (PFOS)] were substantially elevated in the serum, colostrum, and breast milk samples of highly exposed women in the cohort and showed strong correlation. PFHxS and PFOS also contributed the largest fraction of total PFAS on average in colostrum and breast milk. Median TEs varied from 0.9% to 4.3% and were higher for perfluoroalkyl carboxylic acids, including perfluorooctanoic acid, than perfluoroalkane sulfonic acids, including PFHxS and PFOS. TEs varied by exposure level, but there was not a consistent pattern in this variation. PFAS concentrations in the colostrum and breast milk of highly exposed women were higher than the concentrations in low-exposed women, and TEs were of a similar magnitude across exposure categories. This implies that breastfeeding may be an important route of PFAS exposure for breastfeeding infants with highly exposed mothers, although the relative contribution of breastfeeding vs. prenatal transplacental transfer remains to be clarified. https://doi.org/10.1289/EHP11292.